2009
DOI: 10.1261/rna.1533909
|View full text |Cite
|
Sign up to set email alerts
|

A comparative genomics approach identifies a PPR-DYW protein that is essential for C-to-U editing of the Arabidopsis chloroplast accD transcript

Abstract: Several nuclear-encoded proteins containing pentatricopeptide repeat (PPR) motifs have previously been identified to be transfactors essential for particular chloroplast RNA editing events through analysis of mutants affected in chloroplast biogenesis or function. Other PPR genes are known to encode proteins involved in other aspects of organelle RNA metabolism. A function has not been assigned to most members of the large plant PPR gene family. Arabidopsis and rice each contain over 400 PPR genes, of which ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 63 publications
3
123
0
Order By: Relevance
“…Unlike the majority of the previously characterized editing mutants (Okuda et al, 2006(Okuda et al, , 2007(Okuda et al, , 2009Chateigner-Boutin et al, 2008;Kim et al, 2009;Yu et al, 2009;Zhou et al, 2009), which were identified via visible growth or fluorescence phenotypes, these mutants were identified directly via a screen for unedited RNAs. It is striking that of the eight mutants discovered in this way, including RARE1 (Robbins et al, 2009) and MEF1 (Zehrmann et al, 2009), none have growth or The curve shows a typical trace of chlorophyll fluorescence in the wild type and a mutant totally impaired in NDH activity (crr21) (Okuda et al, 2007) compared with traces from otp85 and two independent otp84 mutants (otp84-1 and otp84-2). Leaves were exposed to actinic light (AL) (50 mmol of photons m 脌2 s 脌1 ) for 5 min.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Unlike the majority of the previously characterized editing mutants (Okuda et al, 2006(Okuda et al, , 2007(Okuda et al, , 2009Chateigner-Boutin et al, 2008;Kim et al, 2009;Yu et al, 2009;Zhou et al, 2009), which were identified via visible growth or fluorescence phenotypes, these mutants were identified directly via a screen for unedited RNAs. It is striking that of the eight mutants discovered in this way, including RARE1 (Robbins et al, 2009) and MEF1 (Zehrmann et al, 2009), none have growth or The curve shows a typical trace of chlorophyll fluorescence in the wild type and a mutant totally impaired in NDH activity (crr21) (Okuda et al, 2007) compared with traces from otp85 and two independent otp84 mutants (otp84-1 and otp84-2). Leaves were exposed to actinic light (AL) (50 mmol of photons m 脌2 s 脌1 ) for 5 min.…”
Section: Discussionmentioning
confidence: 96%
“…Investigation of Arabidopsis mutants with such phenotypes has identified a number of nuclear genes suspected to encode RNAediting specificity factors (Kotera et al, 2005;Okuda et al, 2007Okuda et al, , 2009Chateigner-Boutin et al, 2008;Cai et al, 2009;Kim et al, 2009;Robbins et al, 2009;Yu et al, 2009;Zehrmann et al, 2009;Zhou et al, 2009). In each case, loss of one of these factors leads to a specific loss of editing of one or at most a few sites.…”
Section: Introductionmentioning
confidence: 99%
“…RNA extraction and RT-PCR methods were as previously described (4) and chloroplast isolation as described in Hayes and Hanson (55). Primers to amplify the mitochondrial and plastid transcripts have been previously described (4,29,56). Analysis of RNA editing by PPE was done as in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of RNA editing by PPE was done as in ref. 29. The editing extent in maize plastid genes was measured primarily by bulk-sequencing of RT-PCR products amplified with primers listed in Table S4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation